The relationship between intrapreneurial orientation and job performance among academicians in Malaysian public universities - Nik Ismail, Nik Nor Hasimah; Mahmood, Rosli; Ab Rahim, Roslan (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2012)
The main objective of the higher education transformation is to improve the performance of higher education institutions in Malaysia and this demand for an emphasis in competitiveness, creativity, and innovations. Beginning in 1998, five public universities had been corporatized. To initiate this transformation process in the higher education, academicians have very important roles to play and there seem to be a need for them to possess some entrepreneurial values and characteristics. Yet no empirical studies had been conducted on the relationship between intrapreneurial orientation (IO) and job performance among these academicians. This study was conducted to identify the level of IO and its relationship to job performance among academicians in Malaysian public universities. The study adopted a quantitative approach through survey instruments design and the population of the study was the academicians of 20 Malaysian public universities. Data collection was made through questionnaires, and the constructs used were adapted from prior research and already tested for reliability. Three dimensions of IO (innovativeness, risk-taking, and proactiveness) were examined. Principal components factor analysis was engaged to extract and rotate factors and descriptive statistics such as means and standard deviations were used to analyse the demography of respondents and to conduct tests of differences. Multivariate techniques used were correlation and multiple regressions. The findings showed that innovativeness and proactiveness had significant and positive relationship with job performance. This study highlights the importance of factors relating to job performance among academicians in Malaysian public universities.